STUDI LIMIT DIAMETER PADA SISTEM TEBANG PILIH HUTAN ALAM - Hariyatno Dwiprabowo (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
Indonesian Selective Cutting (Tebang Pilih Indonesia) as a silviculture system pays a considerable attention to the growth of seedlings and saplings in the forests as it is considered to represent the fourth generation in the succession of the tropical rain forests. However, there is some question as to how to relate the growth to the detennination of cutting diameter limit quantitatively such that in detennining the diameter limit the growth of the seedlings can be. part of the objective to be considered.With regard to this problem a study was conducted in S. Seruyan Hulu and S. Jelang - S. Delai forests, Central Kalimantan, to examine the relationship between the height of seedlings of meranti species (Shorea spp.) and tress basal area in several sample plots. The relationship expressed in a polynomial regression equation then was used to find the optimal diameter limits with a criterion of maximizing the height of the seedlings.The study showed that the optimal diameter limit was dependent upon the trees basal area and the distribution of trees diameters of the stand.